Kajian Yuridis Argumentum A Contrario Sanksi Dwangsom dalam Putusan Nafkah di Peradilan Agama - Sam’ani Sya’roni (Jurnal Hukum Islam, 2017)
A court verdict regulating living wage that is given to an ex-wife and children after a divorce is still illusory since it lacks imposing authority and legal punishment. A legal plea for its execution faces serious obstacles due to extremely complicated formal requirements. A dwangsom punishment as a compelling money cannot be –from normative perspective- implemented in the punishment of living wage. The focus of this research is to conduct a juridical study of dwangsom legal construction in a verdict regulating living wage through argumentum a contrario (appeal from the contrary). The result confirms that a living wage given to ex-wife and children can be regarded as a “payment-of-certain amount” punishment which consequently cannot be given a dwangsom penalty. However, dwangsom can be implemented in this case through a construction of argumentum a contrario, which is by giving a sentence regulating a prohibition of postponement or avoidance of living wage verdict.